2013
DOI: 10.1371/journal.ppat.1003264
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution of Th1 and Th17 Cells in Adaptive Immunity to Bordetella pertussis: Towards the Rational Design of an Improved Acellular Pertussis Vaccine

Abstract: Whooping cough caused by Bordetella pertussis is a re-emerging infectious disease despite the introduction of safer acellular pertussis vaccines (Pa). One explanation for this is that Pa are less protective than the more reactogenic whole cell pertussis vaccines (Pw) that they replaced. Although Pa induce potent antibody responses, and protection has been found to be associated with high concentrations of circulating IgG against vaccine antigens, it has not been firmly established that host protection induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
323
3
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(364 citation statements)
references
References 64 publications
22
323
3
8
Order By: Relevance
“…Control mice immunized with PBS developed a persistent infection, characteristic of that previously observed in naive mice [5]. Mice immunized with wP or aP+alum-TLR7a had cleared the infection by day 3 post challenge (Fig.3C).…”
Section: Alum-tlr7a Adjuvant Promotes Induction Of Th1 and Th17 Resposupporting
confidence: 68%
See 3 more Smart Citations
“…Control mice immunized with PBS developed a persistent infection, characteristic of that previously observed in naive mice [5]. Mice immunized with wP or aP+alum-TLR7a had cleared the infection by day 3 post challenge (Fig.3C).…”
Section: Alum-tlr7a Adjuvant Promotes Induction Of Th1 and Th17 Resposupporting
confidence: 68%
“…Studies in mice have shown that wP vaccines protect through induction of a mixed Th1/Th17 response, while the aP vaccine promotes Th2/Th17 polarized responses [5,7], with Th2 responses being dispensable for protection. Developed countries are not likely to revert to wP vaccines due to their higher reactogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] It has been long recognized that while WCVs induce a mainly Th1 biased response, the response to ACVs has a distinct Th2 bias. 6 Using an infant baboon model of pertussis, there are clear differences between WCV-and ACV-induced immunity. Both types of vaccines protect the individual against disease but animals vaccinated with ACV were colonized to a higher level and for longer when subsequently challenged with B. pertussis, compared to animals vaccinated with WCV.…”
Section: Resurgencementioning
confidence: 99%